Impacts of the Hutan Kamasyarakatan Social Forestry Program in the Sumberjaya watershed, West Lampung District of Sumatra, Indonesia - Pender, John L.; Suyanto, S.; Kerr, John M.; Kato, Edward (International Food Policy Research Institute, 2008)
This paper investigates the impacts of a social forestry program in Indonesia, Hutan Kamasyarakatan (HKm), based on analysis of a survey of 640 HKm and comparable non-HKm plots in the Sumberjaya watershed of southern Sumatra, and of the households operating those plots. The HKm program provides groups of farmers with secure-tenure permits to continue farming on state Protection Forest land and in exchange for protecting remaining natural forestland, planting multistrata agroforests, and using recommended soil and water conservation (SWC) measures on their coffee plantations. Using farmers? perceptions, econometric techniques, and propensity score matching, we investigated the impacts of the HKm program on perceived land tenure security, land purchase prices, farmers' investments in tree planting and SWC measures, and plot-level profits. A significant fraction of HKm group members are not aware of the program or fully aware of its requirements. Although farmers who are aware of the program perceive its strong effects on tenure security and land values, we found insignificant impacts on the actual purchase prices of plots. Nevertheless, our survey revealed that the HKm program has contributed to increased planting of timber and multipurpose trees. We did not find significant impacts on investments in SWC measures or on soil fertility management practices. HKm has had mixed impacts on profits, with timber trees reducing profitability because timber harvesting is not allowed and multipurpose nontimber trees contributing to increased profits. The policy implications of these findings are also discussed in the paper.--Author's Abstract